1989
DOI: 10.1139/e89-050
|View full text |Cite
|
Sign up to set email alerts
|

Early Permian fossil vertebrate footprints and their stratigraphic setting in megacyclic sequence II red beds, Prim Point, Prince Edward Island

Abstract: Vertebrate trace fossils are reported for the first time from red beds near the top of megacyclic sequence II at Prim Point in southwestern Prince Edward Island. They occur as casts of tetrapod trackways. The ichnocoenose also includes a rich invertebrate ichnofauna. The trackmakers thrived in an area of sparse vegetation and occupied out-of-channel river sediments, most likely crevasse-splay deposits.Amphisauropus latus, represented by three trackways, has been previously reported from Germany, Poland, and Cz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

1989
1989
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…This early Permian age is further supported by the presence of vertebrate fossils obtained from a number of locali ties around Hillsborough Bay (Langston, 1963) and by a recent find at Prim Point of tetrapod trackways in upper Kildare Capes strata interpreted to represent Amplisauropus latus Gilmoreichnus kablikae and possibly Ichniotherium willsi indicating a similar early Permian age (Mossman and Place, 1989). On tenuous evidence Langston (1963, p. 29) suggested that verte brate fossiliferous beds exposed further west at Seacow Head are the same age as those around Hillsborough Bay.…”
mentioning
confidence: 70%
“…This early Permian age is further supported by the presence of vertebrate fossils obtained from a number of locali ties around Hillsborough Bay (Langston, 1963) and by a recent find at Prim Point of tetrapod trackways in upper Kildare Capes strata interpreted to represent Amplisauropus latus Gilmoreichnus kablikae and possibly Ichniotherium willsi indicating a similar early Permian age (Mossman and Place, 1989). On tenuous evidence Langston (1963, p. 29) suggested that verte brate fossiliferous beds exposed further west at Seacow Head are the same age as those around Hillsborough Bay.…”
mentioning
confidence: 70%
“…In marked contrast, none had been described from the neighbouring province of Prince Edward Island nor from the Permian of the Maritimes Basin previous to the discovery in 1984 of the footprints reported here. Since the discovery of trackways described here, a subsequent discovery from Prince Edward Island was published by Mossman and Place (1989). The small but prolifi c trackway-bearing slab here described was discovered at Beech Point, Malpeque Bay by EBU in August of 1984.…”
Section: Introductionmentioning
confidence: 85%
“…156.) A more diminutive ichnospecies, Gilmoreichnus kablikae Haubold, 1974 has been described by Mossman and Place (1989) from Prim Point, Prince Edward Island (Fig. 7) in redbeds mapped as the Kildares Cape Formation (Mossman and Place 1989).…”
Section: Remarks: the Ichnogenus Gilmoreichnus Was Erected Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent phylogenetic analysis (Hancox and Rubidge 2000) focussed on this enigmatic reptile, identifies Eunotosaurus as procolophonid sister group (together with pareiasaurs) of parareptiles, and further as ancestral to anapsids (Reisz and Laurin 1991;Gow and Rubidge 1997). Early Permian procolophons are also well represented in the Maritimes (Mossman and Place 1989;Calder et al 1995;van Allen et al 2005) although nothing recognizable as strictly turtle-like.…”
Section: Introductionmentioning
confidence: 99%